Saving face of the ‘saviour’ : the translations of the Thai Prime Minister’s 2015 press interview and the 2020 national address - Narongdej Phanthaphoommee (Penerbit Universiti Kebangsaan Malaysia, 2023)
Thailand became a military dictatorship in May 2014, after the army deposed the democratically elected government. After being chastised for his lack of legitimacy and appeasing his opposition, Prime Minister Gen Prayut Chan-o-cha began to give official interviews to the international press in his second year in office and intermittently delivered the mandatory live broadcast address to the public. This paper focuses on English translations of Prayut’s 2015 interview with Al-Jazeera and his 2020 televised address. The former is characterised by an impromptu speech that demonstrates his informal speaking style, whereas the latter is a well-scripted address. Using the appraisal framework (Martin & Rose, 2007; Munday, 2012) to analyse both translations, the paper proposes negotiator as an additional resource for examining the speaker’s attitude and the translator’s evaluative choices in the English written version. This investigation demonstrates the translator’s active mediation in both subtitles for media presentation and official translation for national address: maintaining applause for the ruling government while negatively evaluating its critics; modifying the force of attitude; removing any improper features in the premier’s manner of speaking. Despite differences in time and commission, the study argues that both translations support and sustain the Thai government’s aspiration of gaining international attention in order to improve their post-coup image or save the face of the nation’s ‘saviour’, who staged the coup to help the Thai people from the political dispute. Furthermore, the findings on negotiator can be used to inform quality translation training and practice, particularly the translator’s decisionmaking regarding spoken features in political speeches.